2016
DOI: 10.1016/j.jid.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Lentigo Maligna and Lentigo Maligna Melanoma in the Netherlands, 1989–2013

Abstract: Lentigo maligna (LM) is considered a precursor to LM melanoma (LMM). We assessed trends in LM and LMM incidence rates between 1989 and 2013 in the Netherlands, and estimated the risk of an LMM after LM. Data on newly diagnosed LM and LMM were obtained from the Netherlands Cancer Registry and PALGA: Dutch Pathology Registry. Age-standardized incidence rates (European standardized rate), estimated annual percentage changes, and the cumulative incidence of LMM after LM were calculated. Between 1989 and 2013, 10,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 35 publications
1
46
0
2
Order By: Relevance
“…LMMs are usually thin lesions without aggressive growth patterns, explaining why they show excellent survival rates and high prevalence of regression [2, 15]. Nevertheless, they preserve the potential to acquire metastatic characteristics leading to poorer prognosis [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMMs are usually thin lesions without aggressive growth patterns, explaining why they show excellent survival rates and high prevalence of regression [2, 15]. Nevertheless, they preserve the potential to acquire metastatic characteristics leading to poorer prognosis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Lentigo maligna melanoma (LMM) is one of the four subtypes of cutaneous melanomas representing the third most common type with 4–15% [1, 2]. The other three principal subtypes are superficial spreading, nodular, and acral lentiginous melanomas [3].…”
Section: Introductionmentioning
confidence: 99%
“…In northern Europe, the Netherlands, Greveling et al . studied the incidence trends in LM/LMM over a period of 25 years (1989–2013).…”
Section: Discussionmentioning
confidence: 99%
“…If the diagnosis of LM is made at the age of 65, the lifetime risk of developing LMM would be 2.2% without treatment . A recent Dutch study showed that the risk of progression of a LM to LMM is 1.8–2.2% lifetime risk …”
Section: Introductionmentioning
confidence: 99%